More than just enduring – Mental health and well-being among Swedish young adults who ceased self-injuring since adolescence - Claréus, Benjamin (Socialmedicinsk tidskrift, 2023)
Avhandling av Benjamin Claréus, fil. dr., Lunds Universitet, Lund, 2023